The Rat Gambling Task as a model for the preclinical development of treatments for gambling disorder. Issue 2 (4th May 2018) - Di Ciano, Patricia; Le Foll, Bernard
ABSTRACT: Gambling is a harmless pastime for many, but for some it can become problematic with serious social and financial consequences. To date, no pharmacological treatments for gambling disorder have been approved. Progress in this regard is undoubtedly hampered by the lack of established preclinical models that allow for the screening of the potential efficacy of new approaches. The Rat Gambling Task (rGT), based on the Iowa Gambling Task in humans, is a model of some of the decision-making processes involved in gambling. The purpose of the present review is to summarize the literature to date on the use of the rGT for preclinical testing of pharmacological agents. First, the rGT is described and compared to the IGT. Next, validity is examined to establish the rGT as a viable model for preclinical evaluation of new drugs. Finally, the available data on the effects of pharmacological challenges on the rGT are reviewed focusing on dopamine, norepinephrine, serotonin and opioid systems. It is concluded that the rGT may provide a viable preclinical model for new drug development for the treatment of gambling.